Risky Cosmopolitanism: Intimacy and Autoimmunity in Mohsin Hamid's The Reluctant Fundamentalist. Issue 3 (27th May 2017) - Balfour, Lindsay Anne
ABSTRACT: For a novel consistently teetering on the brink of violence, Mohsin Hamid's The Reluctant Fundamentalist begins in a surprisingly benign manner but ultimately offers a sustained interrogation of the possibilities and limits of hospitality in a time of terror. The novel is permeated by references to familiar forms of hospitality and their ultimate failure, yet this article focuses more specifically on the troubling implications The Reluctant Fundamentalist has for a philosophy of hospitality; that is, what appears as a failure of hospitality—the inevitable violence of the novel's conclusion—is actually a provocative and sustained engagement with hospitality in its most pure and terrifying form. Using the figures offered to us by Immanuel Kant and Jacques Derrida, I argue that the novel theorizes a hospitality given even and especially when the face of the other is the irreducible face of death. It exemplifies what Gideon Baker conceptualizes as cosmopolitanism as hospitality —an ethics that opens to difference as Other whatever that other may bring in his infinitely unknowable state. Ultimately, The Reluctant Fundamentalist suggests that if absolute hospitality is an openness to whoever or whatever arrives, then included in that is a hospitality even to the one who comes to kill.